Supporting Factors For The Establishment Of Public Information Disclosure At State Higher Education - Aji, Gilang Gusti; Setyaningrum, Vinda Maya; Islam, Muh. Ariffudin; Indrajayani, Galuh Gita; Firdaus, Dewi Ratnasari (Universitas Islam Negeri Raden Intan Lampung, 2023)
Implementation of good governance in public bodies continues to be pursued in various ways, particularly at state universities. Public information disclosure through the Information Management and Documentation Officer (PPID) and Integrated Service Unit (ULT) is crucial for creating transparent and accountable governance. This study aims to identify supporting factors for successful public information disclosure implementation through these two programs. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis at four state universities with exemplary systems: Brawijaya University, IPB University, Malang State University, and Jakarta State University. The results reveal three key supporting factors: leadership commitment demonstrated through regular evaluation and direct involvement, sustainable innovation in service systems and infrastructure development, and stakeholder synergy between internal and external parties. This research contributes to developing effective public information disclosure strategies in higher education institutions.